Chronic circadian disruption modulates breast cancer stemness and immune microenvironment to drive metastasis in mice - Hadadi, Eva; Taylor, William; Li, Xiao-Mei; Aslan, Yetki; Villote, Marthe; Rivière, Julie; Duvallet, Gaelle; Auriau, Charlotte; Dulong, Sandrine; Raymond-Letron, Isabelle; Provot, Sylvain; Bennaceur-Griscelli, Annelise; et al. (Nature communications, 2020)
Breast cancer is the most common type of cancer worldwide and one of the major causes of cancer death in women. Epidemiological studies have established a link between night-shift work and increased cancer risk, suggesting that circadian disruption may play a role in carcinogenesis. Here, we aim to shed light on the effect of chronic jetlag (JL) on mammary tumour development. To do this, we use a mouse model of spontaneous mammary tumourigenesis and subject it to chronic circadian disruption. We observe that circadian disruption significantly increases cancer-cell dissemination and lung metastasis. It also enhances the stemness and tumour-initiating potential of tumour cells and creates an immunosuppressive shift in the tumour microenvironment. Finally, our results suggest that the use of a CXCR2 inhibitor could correct the effect of JL on cancer-cell dissemination and metastasis. Altogether, our data provide a conceptual framework to better understand and manage the effects of chronic circadian disruption on breast cancer progression. Circadian disruption is implicated in the development of different human cancers. Here the authors show that chronic circadian disruption, through continuous jet lag, only moderately affects primary tumour growth but promotes cancer-cell dissemination and metastasis in a mouse model of spontaneous mammary tumorigenesis.